ANALISIS CURAHAN WAKTU KERJA ANGGOTA RUMAH TANGGA PETANI DAN PENGARUHNYA TERHADAP PERILAKU EKONOMI RUMAH TANGGA PETANI KARET DI PRABUMULIH - Anggrainie, Rona (Jurnal Buana Agribisnis, 2014)
ABSTRACTThe Purpose of this research are: 1 Analyzing the working time household members of rubber farmers in rabumulih. 2. Analyzing the production and income of rubber farmers in Prabumulih. 3. Analyzing the behaviour of households (working time, production and consumption) of rubber farmers in Prabumulih. The results showed that: 1) household time allocation for productive activities which are highest in rubber farming activities (77.71%), then the non-rubber farm (15.27%) and lowest in non-farm activities (7.02%). 2) the largest income of household is from rubber farming (95.31%), then from the non-rubber farming (2.88%) and the smallest is obtained from non-farming activities (1.81%). 3) The behaviour of household working time is affected by total household expenditure, size of rubber land, farm land area of non-rubber, rubber farm income and the number of children under five. The behaviour of household production is influenced by the land area of rubber, non-rubber farming area, the outpouring of family labour on the farm of rubber, fertilizers and pesticides. Household consumption behaviour is influenced by total household income, an outpouring of work hours of household members in the rubber farming and the number of household members.Keywords: rubber farmer, working time, production, and behavior of household